2014
DOI: 10.1002/jsfa.6958
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of volatile aldehydes as discriminating parameters in quality vinegars with protected European geographical indication

Abstract: Aldehyde content of premium quality vinegars is a function of both ageing time and raw material. Their evaluation could be a useful tool with a view to ascertaining vinegar origin and genuineness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Therefore, Lactobacillus, Weissella , Acetobacter , Bacillu s, Lichtheimia , Pediococcus , Oenococcus , Lenconostoc , Pichia , Kazachstania , Xanthomonas, and Brettanomyces may be the main contributors to flavor metabolism. In addition, the compounds in the aging stage may be mainly generated by chemicals such as furfural and pyrazine produced by the Maillard reaction ( Durán-Guerrero et al, 2015 ; Liang et al, 2016 ). However, the metabolic reactions leading to volatile compounds such as benzaldehyde during the aging stage, require further research.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Lactobacillus, Weissella , Acetobacter , Bacillu s, Lichtheimia , Pediococcus , Oenococcus , Lenconostoc , Pichia , Kazachstania , Xanthomonas, and Brettanomyces may be the main contributors to flavor metabolism. In addition, the compounds in the aging stage may be mainly generated by chemicals such as furfural and pyrazine produced by the Maillard reaction ( Durán-Guerrero et al, 2015 ; Liang et al, 2016 ). However, the metabolic reactions leading to volatile compounds such as benzaldehyde during the aging stage, require further research.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study reported that the proportions of aldehydes, including 2-hexenal and hexanal, depended significantly on aging time and the raw materials used to produce the vinegar. [26] Some VOCs in brown rice vinegar, including (Z)-3-hexen-1-ol, (E)-2-hexen-1-ol, 2-furanmethanol, hexyl acetate, and 1-hexanol, were detected only by SPME-Arrow (Table 1). In previous studies, (Z)-3-hexen-1-ol, also known as a green leaf volatile, was considered to be exclusive to wine, tarragon, and apple vinegars.…”
Section: Comparing the Spme-arrow And Conventional Spme Methodsmentioning
confidence: 99%
“…There are other studies focused on GC analysis of balsamic vinegar dealing with the determination of the 13 C/ 12 C glycerol isotope ratio [24], the determination of 2,3-butanediol and 2-hydroxybutanone [17], the analysis of volatile aldehydes [34], the development of new analytical methods for the characterization, authentication, and quality evaluation of BVM [102], the determination of preservatives by the SBSE-TD-GC-MS method [33], and the determination of pesticides by SBSE extraction [30].…”
Section: Other Compounds Identified By Gcmentioning
confidence: 99%
“…[32] Preservatives compounds GC-MS HP-INNOWax SBSE (PDMS) [33] Volatile aldehydes GC-MS Stabilwax SPE (LiChrolut-EN), dichlormethane elu. [34] Volatile compounds GC-MS; FID DB-Wax SPME (CAR/PDMS) [11] Volatile compounds GC-MS; FID CPWax-57CB HSSE-TD (PDMS) [35] Volatile compounds GC-MS; FID DB-Wax SBSE (PDMS) [36] Volatile compounds GC-MS; FID CPSil 5MS SPME (PDMS) [37] Volatile compounds GC-MS Zebron ZB-1701 LLE by diethyl ether [38] Volatile compounds GC-MS Stabilwax SPE (LiChrolut-EN), dichlormethane elu. [10] Volatile compounds GC-MS DB-Wax SBSE (PDMS) [39] Volatile compounds GC-MS Stabilwax SPE (LiChrolut-EN), dichlormethane elu.…”
Section: Introductionmentioning
confidence: 99%